2018
DOI: 10.3389/fpsyg.2018.00159
|View full text |Cite
|
Sign up to set email alerts
|

The Joint Effects of Spatial Cueing and Transcranial Direct Current Stimulation on Visual Acuity

Abstract: The present study examined the mutual influence of cortical neuroenhancement and allocation of spatial attention on perception. Specifically, it explored the effects of transcranial Direct Current Stimulation (tDCS) on visual acuity measured with a Landolt gap task and attentional precues. The exogenous cues were used to draw attention either to the location of the target or away from it, generating significant performance benefits and costs. Anodal tDCS applied to posterior occipital area for 15 min improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…Following the practice, in the test stage, all groups performed the cued Landolt gap task under identical standard conditions, i.e., no groups reported confidence, Figure 1. Results of the Standard Task group have been reported in Bonder et al (2018), this baseline group performance enabled to methodologically compare between the two lines of research.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following the practice, in the test stage, all groups performed the cued Landolt gap task under identical standard conditions, i.e., no groups reported confidence, Figure 1. Results of the Standard Task group have been reported in Bonder et al (2018), this baseline group performance enabled to methodologically compare between the two lines of research.…”
Section: Methodsmentioning
confidence: 99%
“…Arguably, the process of task formation integrates task properties into a combined internal representation, thus enabling formalization of goal-directed strategies, tailored to that representation. Bonder et al (2018) have demonstrated the effect of task formation in the cued Landolt gap task where experimental manipulation exerted in practice caused prominent results in test.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When applied to the primary visual cortex, a-tDCS modulates contrast sensitivity 25,26 , visually evoked potential amplitude 25 and the visual cortex BOLD response 26 . Of particular importance for crowding, a-tDCS can immediately improve Vernier acuity and reduce surround suppression within the near-periphery [27][28][29] , possibly by modulating inhibition within the visual cortex. 27 Lateral masking, a well-established psychophysical paradigm for the assessment of low-level mechanisms that may contribute to crowding, involves the presentation of a central target Gabor patch between two flanker patches 12 .…”
Section: Introductionmentioning
confidence: 99%